Analisis Tahapan Sistem Rekrutmen dan Seleksi Underwriter PT Asuransi Candi Utama - Zulkarnaen, Bagas; Wendra, Wendra (Journal of Emerging Business Management and Entrepreneurship Studies, 2022)
Research shows that a company's greatness is usually determined by mostly 30% of employees, particularly those in the strategic position. In an insurance company, such a position is an underwriter. The insurance company that becomes the object of this research is PT Asuransi Candi Utama. This research uses qualitative analysis as the research method, with the data from interviews, documents, and literature studies. According to the research results, PT Asuransi Candi Utama needs improvements in its recruitment and selection system for underwriters. Recommendations for improving the recruitment system are to add another variant of recruitment methods; as for the selection system, the improvements would include several variants of tests for both cognitive profiles and personality profiles, as well as to add criteria for interview tests. The results of this research can be observed for more research.